The Influence of Technology on Pharmaceutical Care Access at Primary Health Care Facilities in Bahati Sub-County, Nakuru County, Kenya - David Mugothi Kiretai; Susan Mule; Carol Kawila (Journal of Medicine, Nursing and Public health, 2026)
Technology has increasingly become part of pharmaceutical service delivery through tools such as telemedicine, e-prescriptions, mobile health applications, and electronic health records. This study examined the influence of technology on access to pharmaceutical care at primary health care facilities in Bahati Sub County, Nakuru County, Kenya. A mixed-methods design was adopted, combining a patient survey with key informant interviews across fourteen primary health care facilities. Data were collected from 241 patients living with non-communicable diseases (73.5% response rate) and 24 key informants (80.0% response rate), comprising heads of pharmacy, heads of hospitals, the Sub County Pharmacist, and the Sub County Medical Officer of Health. Quantitative data were analysed using descriptive statistics, Pearson correlation, and multiple regression, while qualitative data from interviews were analysed thematically. Patients rated the overall role of technology at a mean of 3.44 (SD = 0.54), indicating modest agreement that digital health tools supported access to medication. Technology showed a positive but modest correlation with pharmaceutical care access (r = 0.243, p < 0.01) and emerged as a statistically significant independent predictor in the regression model (β = 0.156, p = 0.015), after healthcare facility status and socioeconomic factors. Key informants linked technology to improved drug inventory management, faster prescription processing, and improved patient record handling, while patients cited limited access to devices and connectivity as constraints. The study concludes that technology plays a significant but currently constrained role in pharmaceutical care access in Bahati Sub County, and recommends investment in digital infrastructure, structured digital-literacy training for patients and providers, and standardised e-prescription and electronic health record use across facilities.